Is PCSK9 Associated with Plasma Lipid Levels in a Sub-Saharan African Population of Patients with Obesity and Type 2 Diabetes? - Mba CM (Dove Medical Press, 2019)
Camille Maadjhou Mba,1 Wilfred Mbacham,1 Eugène Sobngwi,2,3 Jean Claude Mbanya2,3 1Department of Physiological Sciences/Biochemistry, Faculty of Medicine and Biomedical Sciences, University of Yaoundé 1, Yaoundé, Cameroon; 2Department of Internal Medicine and Specialties, Faculty of Medicine and Biomedical Sciences, University of Yaoundé 1, Yaoundé, Cameroon; 3National Obesity Center and Endocrine and Metabolic Diseases Unit, Yaoundé Central Hospital, Yaoundé, CameroonCorrespondence: Camille Maadjhou MbaDepartment of Physiological Sciences/Biochemistry, Faculty of Medicine and Biomedical Sciences, University of Yaoundé 1, PO Box 1364, Yaoundé, CameroonEmail camilya91@yahoo.frPurpose: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a key regulator of circulating LDL cholesterol. There are inconsistent data in some populations concerning the association between PCSK9, LDL and CRP. The emerging importance of the inhibition of PCSK9 for the treatment of hypercholesterolemia warrants investigations in different populations. The aim of this study from a Sub-Saharan African population was to evaluate the association between PCSK9 and hs-CRP levels and plasma lipid levels in patients with type 2 diabetes (T2D) and obese and lean controls.Patients and methods: A cross-sectional analytical study was conducted in a major hospital in Yaoundé, Cameroon in a cohort of 162 participants (53% females). There were 54 non-obese T2D patients matched for age and sex to 54 obese nondiabetic and 54 nondiabetic lean subjects. PCSK9 level was assessed by sandwich ELISA method and hsCRP by nephelometry.Results: PCSK9 and hs-CRP levels were significantly higher in obese and T2D subjects when compared to lean controls (pr=0.56, p=0.02 and r=0.2 and p=0.1, respectively). Multilinear regression analysis identified BMI as an independent predictor for PCSK9 levels and this association was maintained after adjustment for confounders; adjusted β-coefficient; 36.1 (95% CI; 29.2–47.4). We did not find an association between PCSK9 and any plasma lipid levels in obese and T2D subjects, nor between PCSK9 and hs-CRP levels.Conclusion: Obese and type 2 diabetes subjects have higher PCSK9 levels when compared to lean controls, suggesting that these metabolic states potentially impact PCSK9 levels in Cameroonian patients.Keywords: PCSK9, LDL-cholesterol, type 2 diabetes, obesity